Traumatic Pulmonary Pseudocysts in a Young Dog Following Non-penetrating Blunt Thoracic Trauma - Mulholland, Natosha; Keir, Iain (Frontiers in Veterinary Science, 2019)
Traumatic pulmonary pseudocysts following non-penetrating blunt thoracic trauma is a well-described phenomenon in the human literature, with only one case reported in the veterinary literature. This case report describes a 1.5-year-old male castrated Labrador retriever with findings of pulmonary cyst formation following a road traffic accident via diagnostic imaging modalities. The goal of this report is to expound on the pathophysiology, diagnosis and treatment of this uncommon disease process in the veterinary field.